Evaluasi Sistem Kinerja E-Tracking Pada Aplikasi Transjakarta Menggunakan Metode PIECES - Azriel Yudha Pratama; Mely Mailasari (Journal of Students‘ Research in Computer Science, 2026)
GPS-based E-Tracking technology plays an important role in Transjakarta's operations by ensuring schedule accuracy and providing travel information to passengers. This study aims to evaluate the quality of the E-Tracking system in the Transjakarta application using the PIECES Framework (Performance, Information, Economics, Control, Efficiency, and Service). A mixed-methods approach was employed through a survey of 71 active users and interviews with Command Center officers. The results indicate that the E-Tracking system achieved a very high level of user satisfaction, with an average score of 4.37 (Very Satisfied category). The Information, Economics, Control, and Efficiency dimensions obtained the highest score of 4.40, while the Performance and Service dimensions scored 4.34 and 4.31, respectively. The main issues identified include data latency and the Ghost Bus phenomenon caused by signal disruptions in certain areas. Overall, the E-Tracking system functions effectively in supporting Transjakarta operations, although improvements in infrastructure and data processing are still needed to enhance service quality.